Opportunities for integrating gamification and emerging technologies with direct observation in biology education: A bibliometric analysis - Hery Fajeriadi; Aminuddin Prahatama Putra; Bunda Halang; Gt. Muhammad Irhamna Husin; Nurul Aulia; Muhammad Naufal Azzam; Muhammad Abdi Gusti; Hanisa Hanisa (HAFECS PRESS, 2026)
Digital transformation in higher education has led to the emergence of gamification, direct observation, and new technologies in biology learning, but previous studies have discussed them separately. To date, there has been no bibliometric study that systematically maps the integration of these three approaches. This study aims to analyze global research trends, thematic gaps, and potential integration across topics using a bibliometric approach. Data were retrieved from Google Scholar through the Publish or Perish application using the keywords “gamification,” “emerging technology,” and “biology,” covering publications from 2020 to 2024. A total of 207 relevant articles were analyzed and visualized using VOSviewer to map bibliometric relationships based on keyword co-occurrence, citation networks, and topic evolution. The results indicate a significant increase in publication growth over the past five years, with dominant themes such as artificial intelligence, deep learning, and virtual simulation, reflecting a shift toward emerging and adaptive learning models. Cluster mapping identified four major research groups: digital gamification, data-driven learning, virtual simulation, and implementation-based studies. These findings confirm that international research in biology education is moving toward the synergy of interactivity, analytics, and technology-based experiential learning. Nevertheless, the integration of gamification and direct observation with emerging technologies remains limited, representing a strategic opportunity for future empirical exploration. This study reinforces experiential learning and situated cognition as the basis for integrating interactive digital technology and direct observation practices. These findings also provide strategic direction for the design of adaptive, evidence-based pedagogical innovations in biology education. Abstrak. Transformasi digital dalam pendidikan tinggi mendorong munculnya gamifikasi, pengamatan langsung, dan teknologi baru dalam pembelajaran biologi, namun kajian sebelumnya masih membahasnya secara terpisah. Hingga kini, belum ada studi bibliometric yang memetakan secara sistematis integrasi ketiga pendekatan tersebut. Penelitian ini bertujuan untuk menganalisis tren penelitian global, kesenjangan tematik, serta potensi integrasi antartopik melalui pendekatan bibliometrik. Data diperoleh dari basis Google Scholar menggunakan aplikasi Publish or Perish dengan kata kunci “gamification”, “emerging technology”, dan “biology”, mencakup publikasi tahun 2020–2024. Sebanyak 207 artikel yang relevan dianalisis dan divisualisasikan menggunakan VOSviewer untuk menggambarkan keterkaitan bibliometrik berdasarkan jejaring kata kunci, sitasi, dan evolusi tren riset. Hasil analisis menunjukkan peningkatan publikasi yang signifikan dalam lima tahun terakhir, dengan dominasi tema artificial intelligence, deep learning, dan virtual simulation yang mencerminkan pergeseran riset menuju integrasi teknologi imersif dan pembelajaran adaptif. Pemetaan klaster mengidentifikasi empat kelompok utama, yaitu gamifikasi digital, pembelajaran berbasis data, simulasi virtual, dan penelitian implementatif. Temuan ini menegaskan bahwa riset internasional dalam pembelajaran biologi bergerak ke arah sinergi antara interaktivitas, analitik, dan pengalaman belajar berbasis teknologi. Kajian ini juga mengungkap bahwa integrasi gamifikasi dan pengamatan langsung dengan teknologi baru masih terbatas, sehingga menjadi peluang strategis untuk penelitian lanjutan. Penelitian ini memperkuat dasar experiential learning dan situated cognition sebagai landasan integrasi antara digital interaktif dan praktik observasi langusng. Temuan ini juga memberikan arah strategis bagi perancangan inovasi pedagogis yang adaptif dan berbasis bukti dalam pembelajaran biologi.